2016
DOI: 10.1159/000447589
|View full text |Cite
|
Sign up to set email alerts
|

Diplophonia Disturbs Jitter and Shimmer Measurement

Abstract: Objectives: The aims of this study are to investigate the effects of diplophonia on jitter and shimmer and to identify measurement limitations with regard to material selection and clinical interpretation. Materials and Methods: Four hundred and ninety-eight audio samples of sustained phonations were analyzed. The audio samples were assessed for the grade of hoarseness and the presence of diplophonia. Jitter and shimmer were reported with regard to perceptual ratings. We investigated cycle marker positions exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Although jitter and shimmer have been linked to perceptions of roughness and breathiness, respectively [19], several studies have concluded that they are unreliable indicators of voice quality [41,44,45,46], especially for voices perceived to score highly on measures of Grade, a measure of perceived hoarseness [14]. Furthermore, jitter and shimmer can present as normal in voices that contain subharmonics [47] and are unreliable for diplophonic voices [48,49]. For all participants in the present study, this is evident in those vowels that contain subharmonics but result in normative data (e.g.…”
Section: Perturbation Measures and Perceived Voice Qualitiesmentioning
confidence: 99%
“…Although jitter and shimmer have been linked to perceptions of roughness and breathiness, respectively [19], several studies have concluded that they are unreliable indicators of voice quality [41,44,45,46], especially for voices perceived to score highly on measures of Grade, a measure of perceived hoarseness [14]. Furthermore, jitter and shimmer can present as normal in voices that contain subharmonics [47] and are unreliable for diplophonic voices [48,49]. For all participants in the present study, this is evident in those vowels that contain subharmonics but result in normative data (e.g.…”
Section: Perturbation Measures and Perceived Voice Qualitiesmentioning
confidence: 99%
“…However, during that time, the F0 were decreased to the lowest value of 124.23 Hz and diplophonia emerged after enhanced lower pitch training. Diplophonia was defined as the simultaneous presence of 2 pitches, or the impression of distinct diplophonic beating [28]. Cyclic waveform patterns arose from the beating of 2 signals with different fundamental frequencies.…”
Section: Measurementmentioning
confidence: 99%